A study on relationship between service quality and customer satisfaction towards Stadium Hang Jebat Melaka in 2007 / Noor Azfar Akmal Bahara - Bahara, Noor Azfar Akmal (Faculty of Business and Management, 2007)
The cost of getting new customers is much higher than the cost of maintaining the existing customers. Therefore, it is important for the company to foster customer satisfaction in order to create customer loyalty. This research is about a study on relationship between service quality and customer satisfaction towards Stadium Hang Jebat Melaka in 2007. Element of service quality such as tangibility, reliability, responsiveness, assurance and empathy have been identified in order to investigate whether or not those elements have significant relationship with customer satisfaction.